Formation water geochemistry for carbonate reservoirs in Ordos basin, China: Implications for hydrocarbon preservation by machine learning - Yu, Hongyan; Wang, Z.; Rezaee, Reza; Zhang, Y.; Nwidee, Lezorgia N.; Liu, X.; Verrall, M.; Iglauer, Stefan (ELSEVIER, 2020)
Formation water can in principal be used to identify hydrocarbon reserves. One such potential reserves are the gas reservoirs in the Ordos basin in China. However, there is limited data for this basin; we thus investigated the geochemical properties of a large range of formation water acquired from the Ordovician in the Ordos basin (42 brine samples obtained from different wells at M5 member) and analyzed their chemical characteristics. The results showed that this formation water is associated with a sealed reservoir, which is good for hydrocarbon storage. This is also related to the demonstrated strong diagenetic transformations. We also proposed statistical relationships between these geochemical properties and hydrocarbon storage based on a machine learning method (Decision tree). The results suggest that the salinity, Na+/Cl− ratio, (Cl−-Na+)/Mg2+ ratio, (HCO3−-CO32-)/Ca2+ ratio and Mg2+/Ca2+ ratio highly correlate with the gas preservation. The results thus provide drastically more accurate predictions in terms of where to find gas reservoirs in the Ordos basin, and can thus lead to significantly better exploitation of these resources.